Origin of the Universities (Docentes 2.0 Journal, 2014)
Knowledge, information, education, etc., exists many years before the institution known as the University was formed. Greece and Rome formed a very good education, knowledge and research base, with teachers, students; it was the time of the great scholars, of the great schools and high schools, of the great sages, like Aristotle or Plato, who without existing the term University, knew how to forge an excellent mass of knowledge that to this day influence.
Keywords: Origin; Universidades